Research on Characteristics of Broadband Acoustic Sensor Based on Silicon-Based Grooved Microring Resonator - Jiangong Cui (MDPI AG, 2021)
In order to meet the requirements of having a small structure, a wide frequency band, and high sensitivity for acoustic signal measurement, an acoustic sensor based on a silicon-based grooved microring resonator is proposed. In this paper, the effective refractive index method and the finite element method are used to analyze the optical characteristics of a grooved microring resonator, and the size of the sensor is optimized. The theoretical analysis results show that, when the bending radius reaches 10 μm, the theoretical quality factor is about 106, the sensitivity is 3.14 mV/Pa, and the 3 dB bandwidth is 430 MHz, which is three orders of magnitude larger based on the sensitivity of the silicon-based cascaded resonator acoustic sensor. The sensor exhibits high sensitivity and can be used in hydrophones. The small size of the sensor also shows its potential application in the field of array integration.